2010
DOI: 10.1002/ejlt.200900021
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic compounds and some quality parameters of pumpkin seed oil

Abstract: Pumpkin seed oil has become a recognized source of phenolic compounds. The main aim of this paper was to evaluate the concentration of phenolic compounds and their extraction from pumpkin seed oil. The total phenolics content (TPC) measured in the pumpkin seed oil samples ranged from 24.71 to 50.93 mg GAE/kg of oil. The individual phenolics were tyrosol, vanillic acid, vanillin, luteolin and sinapic acid. Hexane and acetone were the best solvents for the washing step, and methanol for the elution of the phenol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
77
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(94 citation statements)
references
References 28 publications
7
77
6
Order By: Relevance
“…According to the literature, the content of total phenolic compounds in oil is mainly related to the oil from roasted pumpkin seeds, and is reported to range from 0.28 to 2.46 mg GAE/100 g (Tuberoso et al, 2007;Siger et al, 2008). Andjelkovic et al, (2010) reported the contents of phenolics in PSO samples in a range from 2.47 to 5.09 mg GAE/100 g. Also, higher contents of phenolic compounds in a range from 7.33 to 128.84 mg GAE/100 g were reported by Jiao et al, (2014).…”
Section: Antioxidant Activity Datamentioning
confidence: 99%
See 1 more Smart Citation
“…According to the literature, the content of total phenolic compounds in oil is mainly related to the oil from roasted pumpkin seeds, and is reported to range from 0.28 to 2.46 mg GAE/100 g (Tuberoso et al, 2007;Siger et al, 2008). Andjelkovic et al, (2010) reported the contents of phenolics in PSO samples in a range from 2.47 to 5.09 mg GAE/100 g. Also, higher contents of phenolic compounds in a range from 7.33 to 128.84 mg GAE/100 g were reported by Jiao et al, (2014).…”
Section: Antioxidant Activity Datamentioning
confidence: 99%
“…The seeds of pumpkin varieties also exhibit high antioxidant activity. Andjelkovic et al, (2010) reported the concentration of phenolic compounds and that phenolic content ranged from 2.471 to 5.093 mg GAE/100 g. Nederal et al, (2014) concluded that PSOs contain an essential ω-6 fatty acid (18:2, linoleic acid) in the range of 41.51% to 51.55% of total polyunsaturated fatty acids (PUFA).Also, PSO has a high level of γ-tocopherols, phytosterols, and phospholipid bioactive compounds (Jiao et al, 2014;Rezig et al, 2012;Andjelkovic et al, 2010) The genetic factors, extraction technique, cultivation, climate, production and storage conditions of seed oils are critical factors for the content of bioactive compounds (Nawirska-Olszanska et al, 2013). To the best of our knowledge, there is no research in the literature on the assessment of different pumpkin cultivars from the central Anatolia regions of Turkey to determine their potential for commercial and industrial applications.…”
Section: Introductionmentioning
confidence: 99%
“…Plant phenolics also may protect against some forms of cancer (Emmons and Peterson, 2001). Descriptions of the phenolic compounds isolated from pumpkin, pumpkin seeds, or seed oil and their characteristics have been previously published (Andjelkovic et al, 2010). The present study mainly aimed to evaluate the fatty acid contents and antioxidant parameters of seed oils isolated from different pumpkin cultivars.…”
Section: Determination Of Total Phenolic Contentsmentioning
confidence: 99%
“…Total phenol content of the test oils is lower than that reported for olive oil which is in the range of 10 to 30 mg/100 g [15]. Nevertheless, the oils are richer in phenolic compounds than other oils such as that of pumpkin seeds (3.9 ± 2.6 mg/100g) [18]. These compounds have previously been correlated with the oxidative stability of vegetable oils.…”
mentioning
confidence: 72%